2009
DOI: 10.1007/s11262-009-0355-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and genome of Euproctis pseudoconspersa nucleopolyhedrovirus

Abstract: Euproctis pseudoconspersa NPV (EupsNPV) is pathogenic to the tea tussock (E. pseudoconspersa), one of the major pests of tea bushes in East Asia, and has been used to control the pest. Electron microscope observation showed there were two modes for the virions embedded in each polyhedron, single-nucleocapsid and double-nucleocapsid. The EupsNPV genome contained 141,291 bp and had a G + C content of 40.4%. Of 139 potential ORFs predicted from the sequence, 126 had a homology in other baculoviruses; 13 were uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…From the phylogenetic tree, ArdiNPV (indicated by a red star) was classified as a member of Clade II.b Alphabaculoviruses , which forms a well-supported cluster within Clade II.b with 13 viruses, including Hemileuca sp. NPV (HespNPV) [35], Apocheima cinerarium NPV (ApciNPV), Ectropis obliqua NPV (EcobNPV) [36], Orgyia leucostigma NPV (OrleNPV) [37], Euproctis pseudoconspersa NPV (EupsNPV) [12], Sucra jujuba NPV (SujuNPV) [38], Buzura suppressaria NPV (BusuNPV) [33], Hyposidra talaca NPV (HytaNPV) [39], Lambdina fiscellaria NPV (LafiNPV) [40], Clanis bilineata NPV (ClbiNPV) [34], Perigonia lusca single NPV (PeluNPV) [41], Lymantria dispar MNPV (LdMNPV) [42] and Lymantria xylina MNPV (LyxyMNPV) [43]. Although ArdiNPV appears to be most closely related to EupsNPV (Figure 2), the whole-genome similarity between the two viruses was only 57.4% and although their genomes are mostly collinear, there is an inversion comprising genes from orf25 ( dnaJ ) to orf44 ( p47 ) between the two genomes (Figure 3), suggesting ArdiNPV as a novel species of Clade II.b Alphabaculoviruses .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the phylogenetic tree, ArdiNPV (indicated by a red star) was classified as a member of Clade II.b Alphabaculoviruses , which forms a well-supported cluster within Clade II.b with 13 viruses, including Hemileuca sp. NPV (HespNPV) [35], Apocheima cinerarium NPV (ApciNPV), Ectropis obliqua NPV (EcobNPV) [36], Orgyia leucostigma NPV (OrleNPV) [37], Euproctis pseudoconspersa NPV (EupsNPV) [12], Sucra jujuba NPV (SujuNPV) [38], Buzura suppressaria NPV (BusuNPV) [33], Hyposidra talaca NPV (HytaNPV) [39], Lambdina fiscellaria NPV (LafiNPV) [40], Clanis bilineata NPV (ClbiNPV) [34], Perigonia lusca single NPV (PeluNPV) [41], Lymantria dispar MNPV (LdMNPV) [42] and Lymantria xylina MNPV (LyxyMNPV) [43]. Although ArdiNPV appears to be most closely related to EupsNPV (Figure 2), the whole-genome similarity between the two viruses was only 57.4% and although their genomes are mostly collinear, there is an inversion comprising genes from orf25 ( dnaJ ) to orf44 ( p47 ) between the two genomes (Figure 3), suggesting ArdiNPV as a novel species of Clade II.b Alphabaculoviruses .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the complete genome sequence of ArdiNPV was determined and analyzed. Phylogenetic analysis suggested that this virus is a novel Clade II.b Alphabaculovirus , which may be closely related to Euproctis pseudoconspersa nucleopolyhedrovirus (EupsNPV) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The virus is a novel member of a subclade containing eight other baculoviruses, including Apocheima cinerarium NPV (ApciNPV), Clanis bilineata NPV (ClbiNPV) [18] , Ectropis obliqua NPV (EcobNPV) [19] , Euproctis pseudoconspersa NPV (EupsNPV) [20] , Hemileuca sp. NPV (HespNPV) [21] , Lymantria dispar MNPV (LdMNPV) [22] , Lymantria xylina MNPV (LyxyMNPV) [23] and Orgyia leucostigma NPV (OrleNPV) [24] .…”
Section: Resultsmentioning
confidence: 99%
“…The larva of this insect pest can also cause allergic reaction on human skin ( Wang et al 2005 ). Besides chemical control of this pest, environmentally friendly pest control approaches are normally used to reduce insecticide residues in tea products, for instance, nucleopolyhedrovirus ( Tang et al 2009 ). More recently, the development of high-throughput sequencing technologies has facilitated the discovery of other virus species with no obvious pathological signs of infection.…”
mentioning
confidence: 99%